Settlement experiment of spat using three different collectors in two contrasting coastal sites from Chile (SE Pacific Ocean) - Díaz, Christian; Sobenes, Catterina; Cruz Motta, Juan José; Riera, Rodrigo (Frontiers in Marine Science, 2022)
Most of the marine bivalve production comes from aquaculture and only 11% comes from the wild fishery. For example, mussel aquaculture still strongly relies on spat - the recently settled juveniles. Gaps of information on the recruitment and settlement of spat are important drawbacks for the development of mussel aquaculture in several geographic regions. We here study these processes using three collectors (Anchovy mesh, Rope and Raschel mesh) throughout one year in two coastal sites of Central Chile (Coliumo and Punta Lobería) at three depths (2, 4 and 6 m). Five spat species were settled in the collectors, i.e. Aulacomya atra, Choromytilus chorus, Mytilus chilensis, Mytilus galloprovincialis and Semimytilus algosus. Recruitment was consistently higher during summer and autumn at both sites. Different seasonal recruitment patterns were observed regarding the spat species. Spat collection of the former mytilid species occurs from spring to autumn with the exception of M. galloprovincialis in Coliumo and M. chilensis in Punta Lobería. M. galloprovincialis is settled mostly in autumn and summer, and M. chilensis during winter. There were also differences when considering the collector type, mostly due to A. atra and S. algosus which peaked in nylon rope. Spat collection of the commercial species M. chilensis should be preferentially carried out in nylon rope during autumn in Coliumo and summer and autumn in Punta Lobería. During summer and autumn, also S. algosus will be settled. These results will enable the implementation of management measures to promote mytilid culture on the coastal zone of the Biobío region.